A Root Structure Architecture (Rsa) Study On Eggplant (Solanum melongena L.) Inoculated With Arbuscular Mycorrhizal Fungi (AMF) Biofertilizer - Mikee Louissa Yanez; Diana P Paguntalan (Journal of Tropical Mycorrhiza, 2023)
Solanum melongena L. is among the most economically valued horticultural crops globally. In the Philippines, the annual production of this staple crop increases continually. However, several biotic and abiotic factors deteriorate its overall growth and productivity. Recently, the use of sustainable biofertilizers such as arbuscular mycorrhizal fungi (AMF) is gaining interest because of their beneficial impacts on overall plant productivity. One way of examining plant productivity is through root structure architecture (RSA) assessment. Hence, this study aimed to investigate the effects of AMF on the RSA of eggplants to supplement valuable data on its beneficial effects as a biofertilizer. Seedlings were inoculated with four treatment conditions AMF + vermicompost (AMF + V), AMF alone (AMF), NPK fertilizer (NPK), and native soil (C) followed by RSA assessment Results showed that treatments AMF + V and AMF alone significantly promoted lateral root branching. Furthermore, the total diameter and surface area showed a significant increase under treatment AMF + V. Overall, the mycorrhizal-root association presented enhancement towards eggplant RSA which strongly establishes the efficacy of AMF as a promising solution in promoting sustainable agriculture.